2015
DOI: 10.1007/s10096-015-2445-3
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of biofilm formation and virulence of different species of coagulase-negative staphylococci to public health

Abstract: The ability of biofilm formation seems to play an essential role in the virulence of coagulase-negative staphylococci (CNS). The present work aimed to: (a) evaluate the biofilm-forming ability of different strains of CNS field isolates; (b) evaluate their virulence potential through the assessment of the Madin-Darby canine kidney (MDCK) cytotoxicity assay; (c) determine the frequency of biofilm-associated genes among these CNS isolates. Biofilm markers associated with biofilm formation and MDCK cells cytotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 34 publications
(32 reference statements)
5
26
0
Order By: Relevance
“…In the present investigation, the icaA and icaD were evaluated because the detection of these genes implies the biofilm formation by staphylococcal isolates. In addition, these genes regulate the slime production (7,13). In our study, the presence of icaA gene in all tested isolates was associated with the presence of icaD gene and vice versa, which has also been mentioned by other authors (28,34).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In the present investigation, the icaA and icaD were evaluated because the detection of these genes implies the biofilm formation by staphylococcal isolates. In addition, these genes regulate the slime production (7,13). In our study, the presence of icaA gene in all tested isolates was associated with the presence of icaD gene and vice versa, which has also been mentioned by other authors (28,34).…”
Section: Discussionsupporting
confidence: 86%
“…This discrepancy can be attributed to the presence of other molecules involved in the biofilm formation such as ClpP, BHP, and Aae among CoNS isolates (13). Moreover, different studies have demonstrated that the expression of the ica locus is considerably variable and can be affected by many factors, which, in turn, results in the increase or decrease of biofilm production (7). The elucidation of the adhesive processes among clinical isolates might be a solution for developing anti-adhesive approaches to fight with infections due to opportunistic bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was in agreement with that of Osman et al . [21], with an incidence of S. intermedius (31.8%) and S. xylosus (29.5%), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Osman et al . () stated that adherence to a surface and the crystal violet assay are the best phenotypic methods for sensitivity and specificity according to PCR detection of the ica genes. In the present study, different degrees of biofilm formation were obtained for different strains with different combinations of these biofilm genes.…”
Section: Discussionmentioning
confidence: 99%